On the small covering numbers g1(5) (v) - Forbes A.D.; Grannell M.J.; Griggs T.S.; Stanton R.G. (Utilitas Mathematica, 2007)
The minimum number of blocks having maximum size precisely five that is required to cover, exactly once, all pairs of elements from a set of cardinality v is denoted by g1(5) (v). As a prelude to further work, we give the values of g1(5) (v) for v ≤ 25, and construct all designs which attain this bound.